Preventive medicine: domestic repression and foreign revolutionary states. Issue 1 (2nd January 2021) - Linebarger, Christopher
ABSTRACT: Do governments repress in order to defend themselves against the threat posed by the geographic proximity of victorious rebel forces? I theorize that the victory of rebel forces in armed conflict, and the subsequent creation of a revolutionary regime, provides a model for mobilization to would-be rebels and that this, in turn, leads government authorities to deploy domestic repression in order to defend themselves. This relationship is conditional upon the international assertiveness of revolutionary regimes, as well as their geographic proximity to the threatened state. Revolutionary regimes that provide assistance to foreign rebels are regarded as more threatening by status-quo states, as are those that are geographically proximate. I undertake a data analysis of state-year patterns of repression and find significant support for my theoretical expectations. My findings have implications for the study of counter-revolution, supporting the notion that state repression is, in part, a function of international threat.